Fractal geometry description of the permeability of a natural fissured rock. - Miguel, A. F. (2013)
Fractal geometry has become a widely accepted description tool to model the capillary fissure network in rocks. The fractal theory is applied to model the permeability and porosity of a natural fissured rock. The fissured structure is treated as having three fractal dimensions: the fissure breadth, the fissure length and the fissure depth. In a first attempt the permeability model predictions are found to agree satisfactory well with data presented in literature.